Discursive investigation into John's internalised spirit identity and its implication - Dube, Zorodzai (Hervormde teologiese studies, 2016)
What does it mean to live in a society where everything good is located within one ethnicity, and geography? In reading the gospel of John, one gets the impression that faithful disciples, the Holy Spirit and morality are exclusively located within the Johannine community and can only permeate to the outside through the good work of the insiders - the disciples. Everything is asymmetric - morality, ideal disciples and good virtues - these originate from within John's community. Outside John's community, it is darkness that awaits the illuminating lights of John's disciples, without which they will remain in perpetual darkness. Despite recent theories that position John as a missionary and an open community, still it does not remove the asymmetric nature of the gospel. The study builds on views inspired by scholars such as Jonathan Draper (1992:13) to argue that John used the Holy Spirit to naturalise identities. From this perspective and if read from the South African context of racism, ethnicity and gender, John makes the reader think about the consequences and implications of exclusive social boundaries.